2015
DOI: 10.1007/s00253-015-6461-0
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification potential under different fertilization regimes is closely coupled with changes in the denitrifying community in a black soil

Abstract: Preferable inorganic fertilization over the last decades has led to fertility degradation of black soil in Northeast China. However, how fertilization regimes impact denitrification and its related bacterial community in this soil type is still unclear. Here, taking advantage of a suit of molecular ecological tools in combination of assaying the potential denitrification (DP), we explored the variation of activity, community structure, and abundance of nirS and nirK denitrifiers under four different fertilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 46 publications
7
48
0
Order By: Relevance
“…The abundance of denitrifier genes including nirS, nirK and nosZ were greatly enhanced by compost addition, which is consistent with previous studies (Kleineidam et al, 2010;Yin et al, 2015;Cui et al, 2016;Pereg et al, 2018;Tao et al, 2018). Random forest analysis indicated that SOM content contributed greatly to nirS, nirK and nosZ gene abundance.…”
Section: Effect Of Compost Addition On Abundance and Community Of Densupporting
confidence: 91%
See 1 more Smart Citation
“…The abundance of denitrifier genes including nirS, nirK and nosZ were greatly enhanced by compost addition, which is consistent with previous studies (Kleineidam et al, 2010;Yin et al, 2015;Cui et al, 2016;Pereg et al, 2018;Tao et al, 2018). Random forest analysis indicated that SOM content contributed greatly to nirS, nirK and nosZ gene abundance.…”
Section: Effect Of Compost Addition On Abundance and Community Of Densupporting
confidence: 91%
“…However, others observed that organic fertilizers showed no significant effect on AOA, while AOB abundance and composition was sensitive in calcareous desert soils (Tao et al, 2017). In addition, documented publications indicated that the effect of organic application on denitrifiers can be positive (Yin et al, 2015;Cui et al, 2016;Pereg et al, 2018) or neutral (Miller et al, 2008;Sun et al, 2015) in agricultural soils. Such varying observations indicated that there is still need to examine the effect of organic fertilization on ammonia oxidizers and denitrifiers.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that nirK and nirS are positively correlated with increasing soil pH [53], which is in line with measurements conducted in our sampling sites [18] and multivariate analysis showing a significant influence of pH on microbial communities. Previous studies also described distinct distributions of the two different denitrification genes nirK and nirS among taxa, with nirK being associated to Rhizobiales [54]. Accordingly, most detected nirK sequences in our dataset originated from Rhizobiales.…”
Section: Functional Profiles Of Energy and Motility-related Metabolissupporting
confidence: 62%
“…High-throughput sequencing technologies can provide significant insights into species and functional diversity of microbial populations with different fertilizer regimes (Hallin et al, 2009;Ye et al, 2013;Zhao et al, 2014). Recent results suggest that the change of potential denitrification under long-term fertilization regimes was closely related to the shift in denitrifying bacteria communities resulting from the variation of properties in black soil (Yin et al, 2015). In the long term, such modifications may result in shifts in the quality and functionality of the soils (Beauregard et al, 2010).…”
Section: Introductionmentioning
confidence: 98%